Evaluating loyalty in South Africa's hotel industry: The effect of service quality and brand equity - Sharmila Ragunanan; Michael C. Cant; Johannes A. Wiid (Economic Review: Journal of Economics and Business, 2024)
The hotel industry in South Africa is fiercely competitive, with a range of accommodation options from international chains to boutique establishments. Establishing and maintaining customer loyalty is essential for hoteliers to ensure repeat business and stand out in a crowded market. This study aimed to evaluate the effect of service quality and brand equity on customer loyalty in South Africa's hotel industry and explored the mediating effects of tangibles, responsiveness, reliability, empathy, and assurance on customer loyalty through service quality, as well as the mediating effects of brand attachment and brand attitude on customer loyalty through brand equity. Guided by a positivist paradigm, the study employed a quantitative methodology and a descriptive research design. Data was collected via an online survey from 379 respondents and analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to test the hypotheses with SmartPLS version 3. The findings revealed a statistically significant effect of service quality and brand equity on customer loyalty. Furthermore, the findings indicate that customer loyalty mediates the relationship between service quality and brand equity. The study offers valuable insights for hotel managers and marketers, recommending strategies to improve customer loyalty through enhanced service quality, emotional branding efforts, and effective customer loyalty programs. These findings emphasize the importance of exceptional service experiences, robust brand equity, and understanding cultural nuances in consumer behavior, providing actionable insights for achieving a sustainable competitive advantage in the South African hotel industry.
Keywords: M31; M37; 330; brand equity; customer loyalty; service quality; South Africa's hotel industry